"Meu Egbé Governado por Mulher, Iyá Nassô é rainha do Candomblé!”. Análise da narrativa do Livro Abre-alas do GRES Unidos de Padre Miguel de 2025 (Revista Internacional de Folkcomunicação, 2025)
This article analyzes the narrative of the samba-enredo “Egbé Iyá Nassô,” presented by Unidos de Padre Miguel (UPM) at the 2025 Carnival, through the lens of the narrative analysis methodology proposed by Luiz Gonzaga Motta (2013) and Silva (2024). Focusing on the levels of plot, episodes, and the centrality of the character, the main objective is to understand how the samba school constructs, through the symbolic and aesthetic language of carnival, a narrative that rescues and celebrates the figure of Iyá Nassô, priestess and founder of Ilê Axé Iyá Nassô Oká, as the central axis of the story and a symbol of Black female resistance. The results indicate that the narrative transcends the biographical account, transforming Iyá Nassô into an emblem of ancestry, identity, and continuity of the African diaspora. The storyline mobilizes archetypes of the founding mother and the guardian of tradition, revealing carnival as a territory of memory, resistance, and collective meaning-making. It is concluded that, through narrative methodology, the parade constitutes an act of cultural and political communication, reaffirming the power of samba schools as agents of preservation and reinvention of Afro-Brazilian ancestry.